PENGARUH BIAYA TRANSPORTASI, INFLASI, PRODUK DOMESTIK REGIONAL BRUTO TERHADAP EKSPOR NON MIGAS INDONESIA TAHUN 2017-2022 - Amifudin, Ahmad Taufik; Anggraini, Yulia (Investama : Jurnal Ekonomi dan Bisnis, 2024)
The role of export or foreign traade activities in economic development is quite prominent. Export activities can have a positive impact, one of which is expanding market share abrodd. Apart from that, it can establish relationships between countries to meed needs that cannot be produced themselves, and can also incresea the productivity of export activities which make a country produce goods to sell meet foreign needs,. This research found that transportation costs on exports when seen from t test which produced t-statistics 2.352645 > 1.69726 t-table and when seen from the probability value 0.0365 < 0.05. on the inflation variable it can be concluded that it has an insignificant influence on exports, if seen from the probability value it produces 0.1387 > 0.05. while the Gross Regional Domestic Product variables shows that it does not have a signficant influence on exports. When viewed from the t test value it produces a t-statistic of -1.389416 > 1.69726 t-table and when viewed from the probability value 0.1899 > 0.05. meanwhile, if we look simultaneously at transportation costs, the inflation rate, gross regional domestic product has a significant influence on export.